2019
DOI: 10.1021/acsinfecdis.9b00052
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Druggability of Carbapenemases and Broad-Spectrum Inhibitor Discovery

Abstract: Serine and metallo-carbapenemases are a serious health concern due to their capability to hydrolyze nearly all β-lactam antibiotics. However, the molecular basis for their unique broad-spectrum substrate profile is poorly understood, particularly for serine carbapenemases, such as KPC-2. Using substrates and newly identified small molecules, we compared the ligand binding properties of KPC-2 with the noncarbapenemase CTX-M-14, both of which are Class A βlactamases with highly similar active sites. Notably, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 82 publications
1
19
1
Order By: Relevance
“…We included these compounds as positive results because their binding kinetics were distinct from non-binders, and because, as described below, crystal structures suggested that they were likely binders. To further exclude the possibility of non-specific protein binding caused by small molecule aggregation 33,34 , we analyzed compounds 1 and 2 against two unrelated enzymes, CTX-M-14 and KPC-2 Class A β-lactamase 35,36 , in a nitrocefin-hydrolysis assay using the SPR buffer. The compounds showed no inhibition of CTX-M-14 or KPC-2 even when tested at 3 mM concentrations, suggesting that the binding to LpxA and LpxD was specific.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included these compounds as positive results because their binding kinetics were distinct from non-binders, and because, as described below, crystal structures suggested that they were likely binders. To further exclude the possibility of non-specific protein binding caused by small molecule aggregation 33,34 , we analyzed compounds 1 and 2 against two unrelated enzymes, CTX-M-14 and KPC-2 Class A β-lactamase 35,36 , in a nitrocefin-hydrolysis assay using the SPR buffer. The compounds showed no inhibition of CTX-M-14 or KPC-2 even when tested at 3 mM concentrations, suggesting that the binding to LpxA and LpxD was specific.…”
Section: Resultsmentioning
confidence: 99%
“…CTX-M-14 and KPC-2 were purified as previously described 35,36,44 . The hydrolytic activity of CTX-M-14 and KPC-2 was determined using the β-lactamase substrate nitrocefin in a PBS-P+ buffer containing 200 mM phosphate buffer pH 7.4, 27 mM potassium chloride and 1.37 M sodium chloride, 0.5% (v/v) surfactant P20 supplemented with 2% DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Previous design efforts to develop wide-spectrum β-lactamase inhibitors have also relied on the shared function of these divergent enzymes to bind β-lactams, but have not previously targeted Lys for covalent modification. [42][43][44][45][46][47][48][49] This particular Lys residue is conserved in most other B1-subclass metallo-β-lactamases (e.g. NDM, IMP, CcrA, BcII, SPM), but not in VIMs, which have a more distant Arg residue that serves an analogous function.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in KPC-2, like in all SBLs, the process involves the catalytic Ser70, which performs a nucleophilic attack on the β-lactam core. The β−lactam substrate is further stabilized in the active site by an extensive network of interactions [22][23][24]. The first inhibitor active against both SBLs and MBLs classes has, only recently, reached clinical trials [19,20].…”
Section: Introductionmentioning
confidence: 99%